Die afrikanischen Arten der Scymnus fronfalis-Gruppe (Coleoptera, Coccinellidae) - Fürsch, Helmut (Entomologica Fennica, 1990)
This article is mainly based on the collections of M. Nummelin in Kibale forest, Uganda. The new species Scymnus danielssoni, S. kibaliensis and S. nummelini are described and compared with the closely related S. capicola, S. cyclicus, S. declaratus, S. demeteri, S. kibonotensis, S. patruelis , S. scapuliþrus and S. simulans. S. congoanus Mader is a new synonym of S. kibonotensis Weise. Male genitals and outlines of the species are figured and a pictorial key is given.